2023
DOI: 10.1152/ajpgi.00201.2022
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis and reduced small intestinal function are required to induce intestinal insufficiency in mice

Abstract: Extensive bowel resection can lead to short bowel syndrome and intestinal failure. Resection-induced dysbiosis may be related to the specific anatomic site of resection and influences the disease progression. While patients with end-jejunostomy are at high risk for intestinal failure, preservation of the ileocecal valve and colon counteracts this risk. The present study investigated the role of the cecum in maintaining microbial homeostasis after different types of small bowel resection. Male C57BL6/J mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
1
7
0
1
Order By: Relevance
“…This was previously documented in both wild-type and colitis-susceptible IL-10−/− mice subjected to ICR [53,54]. The resection-induced dysbiosis in our study was highly similar to that recently reported in mice [13] and could define a signature of specific taxa. Indeed, analogous changes were measured in three distinct resection models and showed reduced diversity and a dramatic decrease in Muribaculaceae and Akkermansia, two mucus-degrading species [55], which was offset by an increase in Proteobacteria (mostly the aerotolerant E. coli) and Firmicutes, including Clostridiaceae, in both limited ICR, extended ICR and even small bowel resection (SBR) experimental models.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was previously documented in both wild-type and colitis-susceptible IL-10−/− mice subjected to ICR [53,54]. The resection-induced dysbiosis in our study was highly similar to that recently reported in mice [13] and could define a signature of specific taxa. Indeed, analogous changes were measured in three distinct resection models and showed reduced diversity and a dramatic decrease in Muribaculaceae and Akkermansia, two mucus-degrading species [55], which was offset by an increase in Proteobacteria (mostly the aerotolerant E. coli) and Firmicutes, including Clostridiaceae, in both limited ICR, extended ICR and even small bowel resection (SBR) experimental models.…”
Section: Discussionsupporting
confidence: 90%
“…The physiopathology-sustaining postoperative recurrences of Crohn's disease remain unknown, although interactions between the enteric and systemic immune system and the gut microbiota at mucosal sites are highly suggested [8,9]. Additionally, it is also well established that overall intestinal surgeries, including ileocecal resection and colorectal surgery, can strongly modify the gut microbiome structure and affect its functionality [10][11][12][13][14]. Collectively, gut microbiota perturbation is thus central in (i) the contribution of the clinical parameters of Crohn's disease (initiation, maintenance and perpetration of inflammation); (ii) the postoperative recurrence of the disease, defining resilience and remission following surgical intervention; and (iii) drug-based therapeutic responses, considering bidirectional interactions between microbes and active molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial analysis of stool samples collected between postoperative days 2 and 7 in mice undergoing small bowel resection has revealed a reduction in alpha diversity and an increase in Proteobacteria; pathobionts such as Clostridia, Shigella and Enterococcus increased after small bowel resection while Muribaculaceae, Lactobacillus and Lachnospiraceae decreased [60]. In our study, the most profound alterations were found in the colon, with SBS causing increases in Faecalibaculum and Escherichia-Shigella and decreases in Ruminococcaceae.…”
Section: Discussionmentioning
confidence: 44%
“…A major factor influencing its outcome is the absence or presence of the ileocecal valve [58,59]. Berlin and coworkers examined microbial changes of stool samples in a comparison of mice undergoing 50% small bowel resection leaving the ileocecal junction intact (comparable to our method), limited ileocecal resection and extended ileocecal resection [60]. Alpha diversity as assessed by the Shannon index remained stable following 50% small bowel resection at postoperative day 5 and was profoundly decreased following the methods associated with resection of the ileocecal valve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation